A Design of Farmer’s Orange Field Security System Using Microcontroller Based Direct Telephone Technology - Rezki Nalandari; Adi Pratama Putra (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
The development of security system is a positive development on reducing society’s anxiety of criminal act such as theft. The security systems that are being developed today are mostly home security systems, motor cycle and cars. So far, the security system for paddy fields or agricultural fields has been minimal studied. So far, security system in farming land has been studied but in minimum frequency, such as in orange field where thefts often occur even farmers had surrounded their farming land with fences. This device made of Pir Sensor that could detect humans, it uses ATmeg328P-PU as the CPU, SIM 800L as media or device in sending messages and battery as power source. Designing this device is easy enough and affordable, this device capable in calling registered phone number in pseudecode that had been input into the program.